Synthesis and evaluation of inhibitors targeting Coenzyme : a biosynthesis and metabolism in Staphylococcus aureus - Van der Westhuyzen, Renier (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD)--University of Stellenbosch, 2010.